Identification of Cosalane as an Inhibitor of Human and Murine CC–Chemokine Receptor 7 Signaling via a High-Throughput Screen. (December 2018) - Hull-Ryde, Emily A.; Porter, Melissa A.; Fowler, Kenneth A.; Kireev, Dmitri; Li, Kelin; Simpson, Catherine D.; Sassano, Maria F.; Suto, Mark J.; Pearce, Kenneth H.; Janzen, William; Coghill, James M.
CC–chemokine receptor 7 (CCR7) is a G protein–coupled receptor expressed on a variety of immune cells. CCR7 plays a critical role in the migration of lymphocytes into secondary lymphoid tissues. CCR7 expression, however, has been linked to numerous disease states. Due to its therapeutic relevance and absence of available CCR7 inhibitors, we undertook a high-throughput screen (HTS) to identify small-molecule antagonists of the receptor. Here, we describe a robust HTS approach using a commercially available β-galactosidase enzyme fragment complementation system and confirmatory transwell chemotaxis assays. This work resulted in the identification of several compounds with activity against CCR7. The most potent of these was subsequently determined to be cosalane, a cholesterol derivative previously designed as a therapeutic for human immunodeficiency virus. Cosalane inhibited both human and murine CCR7 in response to both CCL19 and CCL21 agonists at physiologic concentrations. Furthermore, cosalane produced durable inhibition of the receptor following a cellular incubation period with subsequent washout. Overall, our work describes the development of an HTS-compatible assay, completion of a large HTS campaign, and demonstration for the first time that cosalane is a validated CCR7 antagonist. These efforts could pave the way for new approaches to address CCR7-associated disease processes.